Long-term intermittent feeding restores impaired GR signaling in the hippocampus of aged rat. Issue 149 (May 2015) - Tesic, Vesna; Perovic, Milka; Lazic, Divna; Kojic, Snezana; Smiljanic, Kosara; Ruzdijic, Sabera; Rakic, Ljubisav; Kanazir, Selma
Highlights: Long-term EOD feeding reverts age-induced GR decrease in the rat hippocampus. EOD feeding increases nuclear localization of GR in the hippocampus of aged rats. EOD feeding promotes GR signaling in the rat hippocampus during aging. Abstract: Diminished glucocorticoid signaling is associated with an age-related decline in hippocampal functioning. In this study we demonstrate the effect of intermittent, every other day (EOD) feeding on the glucocorticoid hormone/glucocorticoid receptor (GR) system in the hippocampus of middle-aged (18-month-old) and aged (24-month-old) Wistar rats. In aged ad libitum -fed rats, a decrease in the level of total GR and GR phosphorylated at Ser 232 (pGR) was detected. Conversely, aged rats subjected to EOD feeding, starting from 6 months of age, showed an increase in GR and pGR levels and a higher content of hippocampal corticosterone. Furthermore, prominent nuclear staining of pGR was observed in CA1 pyramidal and DG granule neurons of aged EOD-fed rats. These changes were accompanied by increased Sgk-1 and decreased GFAP transcription, pointing to upregulated transcriptional activity of GR. EOD feeding also induced an increase in the expression of the mineralocorticoid receptor. Our results reveal that intermittent feeding restores impaired GR signaling in the hippocampus of aged animals by inducing rather than by stabilizing GR signaling during aging.